Combined use of sensory methods for the selection of root, tuber and banana varieties acceptable to end-users - Bechoff, A.; Adinsi, L.; Newilah, G.N.; Nakitto, M.; Deuscher, Z.; Ssali, R.T.; Chijioke, Alamu Ugo; Khakasa, E.; Nowakunda, K.; Bouniol, A.; Dufour, D.; Bugaud, C. (Wiley, 2024)
BACKGROUND The assessment of user acceptability in relation to crop quality traits should be a full part of breeding selection programs. Our methodology is based on a combination of sensory approaches to evaluate the sensory characteristics and user acceptability of root, tuber and banana (RTB) varieties.